Iron-based nanocatalyst for the acceptorless dehydrogenation reactions - Jaiswal, Garima; Landge, Vinod G.; Jagadeesan, Dinesh; Balaraman, Ekambaram (Nature Communications, 2017)
Development of sustainable catalytic systems for fundamentally important synthetic transformations and energy storage applications is an intellectually stimulating challenge. Catalytic dehydrogenation of feedstock chemicals, such as alcohols and amines to value-added products with the concomitant generation of dihydrogen is of much interest in the context of hydrogen economy and is an effective alternative to the classical oxidation reactions. Despite a number of homogeneous catalysts being identified for the acceptorless dehydrogenation, the use of high price and limited availability of precious metals and poor recovery of the catalyst have spurred interest in catalysis with more earth-abundant alternatives, especially iron. However, no report has described a reusable iron-based heterogeneous catalyst for oxidant-free and acceptorless dehydrogenation reactions. Here we replace expensive noble metal catalysts with an inexpensive, benign, and sustainable nanoscale iron catalyst for the efficient acceptorless dehydrogenation of N-heterocycles and alcohols with liberation of hydrogen gas.

Nickel-catalyzed N-vinylation of heteroaromatic amines via C-H bond activation - Landge, Vinod G.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2017)
Here, we report a ligand- and reductant-free nickel-catalyzed N-vinylation of heteroaromatic amines using biorenewable p-cymene as a solvent. This unprecedented cross-coupling strategy has high functional group tolerance (halides, alkoxy, cyano, chiral motif, etc.) and proceeded via C-H bond activation.
Keywords: Alkylation; Amination Reactions; Anilines; Aryl Chlorides; halides; Monoarylation; O Bonds; Precatalyst; Pyrimidines; Removeble Directing Group

Unified strategy for silver-, base-, and oxidant-free direct arylation of C-H bonds - Sahoo, Manoj K.; Midya, Siba P.; Landge, Vinod G.; Balaraman, Ekambaram (Green Chemistry, 2017)
Here, we report a dual catalytic approach for room temperature direct arylation of C-H bonds with aryldiazonium salts as a simple aryl group donor, also working as an internal oxidant via C-N-2 bond cleavage. This unified strategy has been achieved by the synergistic combination of visible-light metal-free photoredox and palladium catalysis under silver-, base-and/or additive-free conditions. The broad substrate scope, functional group tolerance, excellent regioselectivity and redox-neutral conditions of this process make it attractive for the effective synthesis of a wide range of important N-heterocyclic commodities such as dibenzo [b,d]azepine, carbazole and phenanthridine.

Cobalt-catalyzed acceptorless dehydrogenative coupling of aminoalcohols with alcohols: direct access to pyrrole, pyridine and pyrazine derivatives - Midya, Siba P.; Landge, Vinod G.; Sahoo, Manoj K.; Rana, Jagannath; Balaraman, Ekambaram (Chemical Communications, 2018)
Here, the first example is reported of a new, molecularly defined SNS-cobalt(II) catalyst for the acceptorless dehydrogenative coupling (ADC) of unprotected amino alcohols with secondary alcohols leading to pyrrole and pyridine derivatives.

Direct access to N-alkylated amines and imines via acceptorless dehydrogenative coupling catalyzed by a cobalt(ii)-NNN pincer complex - Midya, Siba P.; Pitchaimani, Jayaraman; Landge, Vinod G.; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
A simple, phosphine-free Co(ii)-NNN pincer complex catalyzed direct N-alkylation of anilines with alcohols via hydrogen auto-transfer (HA) and selective acceptorless dehydrogenative coupling (ADC) of benzylamines with alcohols affording imines with the liberation of molecular hydrogen and water is reported.

Manganese catalyzed N-alkylation of anilines with alcohols: ligand enabled selectivity - Landge, Vinod G.; Mondal, Akash; Kumar, Vinit; Nandakumar, Avanashiappn; Balaraman, Ekambaram (Organic and biomolecular chemistry, 2018)
Ligand enabled Earth-abundant manganese catalyzed N-alkylation of amines with alcohols via a hydrogen auto-transfer strategy is reported. The choice of the ligand plays a significant role in the alcohol reactivity (aliphatic or aromatic) toward N-alkylation reactions.

Pd(II)-Catalyzed gamma-C(sp(3))-H alkynylation of amides: selective functionalization of R chains of amides (RC)-C-1(O)NHR - Landge, Vinod G.; Parveen, Ayisha; Nandakumar, Avanashiappan; Balaraman, Ekambaram (Chemical Communications, 2018)
The gamma C(sp(3))-H bond alkynylation of R chains of amides (RC)-C-1(O)NHR, a fundamental class of synthetic substrates, has not been accomplished to date. Here, the first example of palladium(ii)-catalyzed alkynylation of an unactivated gamma C(sp(3))-H bond of alkyl amides (cyclic, linear, and amino acids) is reported. The kinetic experiment shows that the rate of the reaction depends on the coupling partners and the amides. Late-stage diversification of alkynylated amides was developed by utilizing amine and alkyne functionalities.

Phosphine-free cobalt pincer complex catalyzed Z-selective semi-hydrogenation of unbiased alkynes - Landge, Vinod G.; Pitchaimani, Jayaraman; Midya, Siba P.; Subaramanian, Murugan; Madhu, Vedichi; Balaraman, Ekambaram (Catalysis Science & Technology, 2018)
Herein, we report a novel, molecularly defined NNN-type cobalt pincer complex catalyzed transfer semi-hydrogenation of unbiased alkynes to Z-selective alkenes. This unified process is highly stereo-and chemo-selective and exhibits a broad scope as well as wide functional group tolerance. Ammonia-borane (AB), a bench-stable substrate with high gravimetric hydrogen capacity, was used as a safe and practical transfer hydrogenating source.

Molecular cobalt(II) complexes for tau polymerization in Alzheimer's disease - Gorantla, Nalini Vijay; Landge, Vinod G.; Nagaraju, Pramod Gudigenahally; Priyadarshini, Poornima C. G.; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (ACS Omega, 2019)
Tau is an axonal protein known to form abnormal aggregates and is the biomarker of Alzheimer's disease. Metal-based therapeutics for inhibition of Tau aggregation is limited and rarely reported in contemporary science. Here, we report the first example of rationally designed molecular cobalt(II)-complexes for effective inhibition of Tau and disaggregation of preformed Tau fibrils. The mechanistic studies reveal that prevention of Tau aggregation by cobalt-based metal complexes (CBMCs) is concentration-dependent and Tau seldom exhibits conformational changes. Interestingly, CBMCs play dual role in causing disassembly of preformed aggregates as well as inhibition of complete Tau aggregation. Furthermore, CBMCs were nontoxic and maintained the tubulin network intact. CBMCs also prevented okadaic acid-induced toxicity in SH-SY5Y cells thus, preventing hyperphosphorylation of Tau. We believe that this unprecedented finding by the newly developed molecular complexes has a potential toward metal-based therapeutics for Alzheimer's disease.

Nickel(ii)-catalyzed direct olefination of benzyl alcohols with sulfones with the liberation of H-2 - Landge, Vinod G.; Yadav, Vinita; Subaramanian, Murugan; Dangarh, Pragya; Balaraman, Ekambaram (Chemical Communications, 2019)
A nickel(II)-catalyzed direct olefination of benzyl alcohols with sulfones to access various terminal and internal olefins with the liberation of hydrogen gas is reported.

Iron-catalyzed direct julia-type olefination of alcohols - Landge, Vinod G.; Babu, Reshma; Yadav, Vinita; Subaramanian, Murugan; Gupta, Virendrakumar; Balaraman, Ekambaram (Journal of Organic Chemistry, 2020)
Herein, we report an iron-catalyzed, convenient, and expedient strategy for the synthesis of styrene and naphthalene derivatives with the liberation of dihydrogen. The use of a catalyst derived from an earth-abundant metal provides a sustainable strategy to olefins. This method exhibits wide substrate scope (primary and secondary alcohols) functional group tolerance amino, nitro, halo, alkoxy, thiomethoxy, and S- and N-heterocyclic compounds) that can be scaled up. The unprecedented synthesis of 1-methyl naphthalenes proceeds via tandem methenylation/double dehydrogenation. Mechanistic study shows that the cleavage of the C-H bond of alcohol is the rate-determining step.

Manganese-catalyzed alpha-olefination of nitriles with secondary alcohols - Yadav, Vinita; Landge, Vinod G.; Subaramanian, Murugan; Balaraman, Ekambaram (ACS Catalysis, 2020)
An expedient catalytic approach for alpha-olefination of nitriles using secondary alcohols with the liberation of molecular hydrogen and water as the only byproducts is reported. This reaction is catalyzed by a molecularly defined manganese(I) pincer complex and operates in the absence of any hydrogen acceptors. A broad range of substrates including cyclic, acyclic, and benzylic alcohols, as well as various nitrile derivatives, such as arylmethyl and heteroarylmethyl nitriles, are employed in the reaction to provide a diverse range of alpha-vinyl nitriles in good to excellent yields. Mechanistic studies showed that the reaction proceeds via dehydrogenative pathway and the activation of alpha(C-H) bond of the alcohol is the rate-determining step.
Keywords: acceptorless dehydrogenation; Alcohol; alpha-olefination; Hydrogen; manganese